Advanced Carbon for Flexible and Wearable Electronics. Issue 9 (9th October 2018) - Wang, Chunya; Xia, Kailun; Wang, Huimin; Liang, Xiaoping; Yin, Zhe; Zhang, Yingying
Abstract: Flexible and wearable electronics are attracting wide attention due to their potential applications in wearable human health monitoring and care systems. Carbon materials have combined superiorities such as good electrical conductivity, intrinsic and structural flexibility, light weight, high chemical and thermal stability, ease of chemical functionalization, as well as potential mass production, enabling them to be promising candidate materials for flexible and wearable electronics. Consequently, great efforts are devoted to the controlled fabrication of carbon materials with rationally designed structures for applications in next‐generation electronics. Herein, the latest advances in the rational design and controlled fabrication of carbon materials toward applications in flexible and wearable electronics are reviewed. Various carbon materials (carbon nanotubes, graphene, natural‐biomaterial‐derived carbon, etc.) with controlled micro/nanostructures and designed macroscopic morphologies for high‐performance flexible electronics are introduced. The fabrication strategies, working mechanism, performance, and applications of carbon‐based flexible devices are reviewed and discussed, including strain/pressure sensors, temperature/humidity sensors, electrochemical sensors, flexible conductive electrodes/wires, and flexible power devices. Furthermore, the integration of multiple devices toward multifunctional wearable systems is briefly reviewed. Finally, the existing challenges and future opportunities in this field are summarized. Abstract : Advances toward understanding the potential of carbon materials for flexible and wearable electronics are reviewed. This encompasses the latest developments in the controlled fabrication of carbon materials with rationally designed structures and their applications in flexible devices including physiological sensors, biochemical sensors, conductive electrodes/wires, power devices, and integrated systems. Current challenges and future prospects in the field are also summarized.